(untitled) (Research, Society and Development, 2022)
Intervention research, of qualitative approach, on the development of a process of continuing education in health, with the theme of prevention of falls in the elderly, carried out with Community Health Agents (CHA) working in one of the territories of the Family Health Strategy of a city in the interior of Ceará. Participant observation, questionnaires, and audio recording were used as instruments of data collection. To describe the results, the data were submitted to content analysis of the thematic analysis type proposed by Minayo. It was noticed a meeting context with some difficulties in the understanding and identification of the team about the risk factors for falls in the elderly. The intervention provided the understanding about these factors, as well as about the possibilities of preventing falls, indicating the possible adaptation needs that must occur in the home environment. The importance of the co-responsibility of the family in elderly care is highlighted.